Dutch juvenile idiopathic arthritis patients, carers and clinicians create a research agenda together following the James Lind Alliance method: a study protocol - Schoemaker, Casper G.; Armbrust, Wineke; Swart, Joost F.; Vastert, Sebastiaan J.; van Loosdregt, Jorg; Verwoerd, Anouk; Whiting, Caroline; Cowan, Katherine; Olsder, Wendy; Versluis, Els; van Vliet, Rens; Fernhout, Marlous J.; et al. (Pediatric rheumatology online journal, 2018)
Research on Juvenile Idiopathic Arthritis (JIA) should support patients, caregivers/parents (carers) and clinicians to make important decisions in the consulting room and eventually to improve the lives of patients with JIA. Thus far these end-users of JIA-research have rarely been involved in the prioritisation of future research. Dutch organisations of patients, carers and clinicians will collaboratively develop a research agenda for JIA, following the James Lind Alliance (JLA) methodology. In a 'Priority Setting Partnership' (PSP), they will gradually establish a top 10 list of the most important unanswered research questions for JIA. In this process the input from clinicians, patients and their carers will be equally valued. Additionally, focus groups will be organised to involve young people with JIA. The involvement of all contributors will be monitored and evaluated. In this manner, the project will contribute to the growing body of literature on how to involve young people in agenda setting in a meaningful way. A JIA research agenda established through the JLA method and thus co-created by patients, carers and clinicians will inform researchers and research funders about the most important research questions for JIA. This will lead to research that really matters.